A quality improvement initiative project to evaluate a newborn hearing screening program in a Baby-Friendly Hospital Initiative setting - Stacey R. Lim; Sandra S. Newcomb (Hygeia Press di Corridori Marinella, 2015)
Hearing loss present from birth can have a detrimental impact on later language and educational outcomes. Newborn hearing screening has allowed early identification and intervention of hearing loss, giving children the opportunity to develop age-appropriate language skills. The aim of this quality initiative study was to evaluate the quality of the newborn hearing screening program in the context of a newly implemented Baby-Friendly Hospital Initiative Program at Summa Health System Akron City Hospital. The goals were (1) to determine whether screening environment (mother's room vs. nursery) affected screening results, (2) to identify challenges and positive outcomes encountered by the audiologists, and (3) to ensure that Pass/Refer rates met state standards. A Quest Technologies sound level meter (Model 1800; St. Paul, MN, USA) was used to measure noise levels in the nursery rooms where newborns were tested. The length of screening time was determined using a calibrated SP® Traceable® (ISO 17025) stopwatch (McGraw Park, IL, USA). Pass/Refer rates and observed challenges and benefits were noted. All well-baby infants born in the month of February 2013 (n = 101) were included, and Pass/Refer results were compared to those in years 2008-2012. Noise levels in the mother's room did not appear to negatively affect the Pass/Refer rates. Some challenges were present, including interruptions and louder environmental noise. This protocol was considered appropriate for assessing a hearing screening program in a Baby-Friendly Hospital Initiative (BFHI) setting. Benefits of performing hearing screening in the mother's room included test transparency for parents and the ability to immediately discuss the results. Results obtained in the mother's room were comparable to past results obtained in the nursery. Noise levels in the screening rooms and challenges should be noted, to ensure accuracy of screening results.